(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic efficacy of acupressure massage combined with electrical pulse therapy in the treatment of neck and shoulder pain caused by cervical spondylosis. Subjects and Methods: A clinical intervention study with pre- and post-treatment comparison was conducted on 60 inpatients with neck and shoulder pain due to cervical spondylosis at the Department of Traditional Medicine and Rehabilitation, Lang Giang Medical Center, Bac Ninh, from April 2025 to October 2025. The patients were divided into two groups: the study group (30 patients) treated with acupressure massage combined with electrical pulse therapy, and the control group (30 patients) treated with acupressure massage alone. Results: Pain relief efficacy according to the Visual Analog Scale (VAS): After 8 days of treatment, the mean VAS score in the study group decreased from 6,13 ± 1,83 to 3,93 ± 0,98, and in the control group from 6,10 ± 1,69 to 4,53 ±1,19 (p < 0.05). Efficacy in improving the Range of Motion (ROM): The mean ROM score in the study group decreased from 14,67±4,14 to 8,87±4,14; in the control group, it decreased from 13,60±4,31 to 9,73±3,50 (p < 0.05). Overall treatment outcomes after 8 days: No cases achieved excellent results in either group; in Group 1, 10% achieved good results and 36.7% fair results, whereas in Group 2, there were no good results and 63.3% achieved fair results (p < 0.05). Conclusion: Combined acupressure and electrotherapy shows better short-term outcomes in pain reduction, muscle spasm relief, and cervical ROM improvement than acupressure alone for patients with cervical spondylosis.